PENERAPAN MODEL â€œUTAUTâ€ UNTUK MENGETAHUI FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MAHASISWA DALAM PENERIMAAN LOGBOOK DIGITAL - Ni Luh Ketut Suardani; Ni Luh Gede Ari Kresna Dewi; Dewa Ayu Ketut Surinati; Ni Nyoman Hartati; Suratiah Suratiah; Nengah Runiari (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2026)
Digitalization logbook filling using QR Code is one of the efforts made to improve the quality of service in laboratory management. The use of this digital system needs to be evaluated to obtain feedback from users towards improvement. Therefore, it is very important to know the level of user acceptance, identify factors that can influence user interest and behavior in utilizing digital logbooks. The purpose of this study was to determine the factors that influence student interest and acceptance behavior towards the digital logbook filling system using the UTAUT method. This research is a quantitative descriptive study. The sampling technique used in this study was nonprobality sampling, namely purposive sampling with a sample size of 67 people. Data were collected using a questionnaire uploaded via Google Drive. Data analysis used multiple linear regression analysis. The results showed that not all variables had a significant effect on student behavior in filling out digital logbooks. The variables in the UTAUT model that significantly influence Behavioral Intention (BI) are Social Influence with a p-value of 0.001, and the Facilitating Conditions variable has a significant effect with a p-value of 0.000 on students' Use Behavior in using the digital logbook filling system. Suggestions are needed for ongoing policy support to integrate the digital logbook system into the practical learning process in the laboratory, as well as ensuring the availability of supporting facilities and infrastructure and technical assistance for users.